Comparison of different glycemic control indicators on incidence of acute kidney injury and long-term mortality in critically ill patients with atherosclerotic cardiovascular disease: A retrospective cohort study - Dan Zhang; Lin Shi; Jia Wang (PLoS ONE, 2026)
Background Advanced glycemic metrics may better reflect glucose dysregulation in critically ill patients than conventional indicators, but their comparative predictive value for adverse outcomes in atherosclerotic cardiovascular disease (ASCVD) patients remains unclear. Methods This retrospective study using the MIMIC-IV database assessed associations between stress hyperglycemia ratio (SHR), hemoglobin glycation index (HGI), and glycemic variability (GV) with acute kidney injury (AKI) and 365-day mortality in 2,820 ASCVD patients. Multivariable regression models, restricted cubic splines, and ROC curves evaluated predictive performance. Results During ICU stay, 38.4% developed AKI, and 17.9% died within one year. GV showed the strongest association with both AKI (Q4 vs. Q1, OR=4.98, 95%CI:3.00–8.26, P < 0.001) and mortality (Q3 vs. Q1, HR = 1.77, 95%CI:1.19–2.63, P = 0.005). SHR was associated with increased AKI risk (Q4 vs. Q2, OR=1.47, 95%CI:1.12–2.19, P = 0.04) and mortality (Q4 vs. Q2, HR = 1.26, 95%CI:1.06–1.69, P = 0.01), while HGI showed inverse association with mortality (Q4 vs. Q1, HR = 0.71, 95%CI:0.53–0.93, P = 0.01). GV yielded the highest predictive accuracy for AKI (AUC = 0.69) and mortality (AUC = 0.62). Subgroup analyses confirmed robustness across demographics. Conclusions Among critically ill ASCVD patients, GV outperformed SHR and HGI in predicting AKI and long-term mortality, underscoring its prognostic utility and supporting individualized glucose management in ICU settings.